Financial incentives to improve uptake of partner services for sexually transmitted infections in Zimbabwe antenatal care: protocol for a cluster randomised trial [version 1; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Ethel Dauya; Chido Dziva Chikwari; Rashida A. Ferrand; Tsitsi Bandason; Victoria Simms; Constance RS. Mackworth-Young; Joseph D. Tucker; Kevin Martin; Francis Ndowa; Anna Machiha; Katharina Kranzer; Sarah Bernays; et al. (Wellcome Open Research, 2023)
Introduction: Sexually transmitted infections (STIs) such as chlamydia, gonorrhoea, trichomoniasis, and syphilis, are associated with adverse birth outcomes. Treatment should be accompanied by partner services to prevent re-infection and break cycles of transmission. Partner services include the processes of partner notification (PN) as well as arranging for their attendance for testing and/or treatment. However, due to a complex mix of cultural, socio-economic, and health access factors, uptake of partner services is often very low, in many settings globally. Alternative strategies to facilitate partner services are therefore needed. The aim of this study is to assess the effect of a small financial incentive on improving uptake of partner services for STIs as part of  antenatal care (ANC) services in Zimbabwe. Methods and analysis: This trial will be embedded within a prospective interventional study in Harare, aiming to evaluate integration of point-of-care diagnostics for STIs into ANC settings. One thousand pregnant women will be screened for chlamydia, gonorrhoea, trichomoniasis, and syphilis. All individuals with STIs will be offered treatment, risk reduction counselling, and client PN. Each clinic day will be randomised 1:1 to be an incentive or non-incentive day. On incentive days, participants diagnosed with a curable STI will be offered a PN slip, that when returned will entitle their partners to $3 (USD) in compensation. On non-incentive days, regular PN slips with no incentive are provided. The primary outcome measure is the proportion of individuals with at least one partner who returns for partner services based on administrative records. Secondary outcomes will include the number of days between index case diagnosis and the partner attending for partner services, uptake of PN slips by pregnant women, adverse birth outcomes in index cases, partners who receive treatment, and intervention cost. Registration: Pan African Clinical Trials Registry: PACTR202302702036850 (Approval date 18th February 2022).